Uji Efektivitas Ekstrak Daun Twandokulo (Kleinhovia hospita Linn) Terhadap pertumbuhan Bakteri Streptococcus mutans ATCC 25175 Penyebab Karies Gigi - Nur Awalia Putri Zainal; Ainun ayu yuniar; Angriani Fusvita; Rein Rahmat (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2025)
leaf is one of the local medicinal plants of Southeast Sulawesi, which has several benefits. One of the benefits of the Kleinhovia hospita Linn plant is as an antibacterial. The purpose of this study was to determine the antibacterial effectiveness of tawandokulo leaf extract (Kleinhovia hospita Linn) on the inhibition zone of Streptcoccus mutans ATCC 25175 bacteria. This research is a laboratory experiment to see the antibacterial effectiveness test of tawandokulo leaf extract (Kleinhovia hospita Linn) against Streptcoccus mutans ATCC 25175 bacteria at various concentrations namely 20%, 40%, 60%, positive control Amoxcilin 0.001%, negative control DMSO. Tawandokulo leaf extract was obtained from maceration extraction using ethanol solvent. This study used the agar well diffusion method, incubated at 37oC for 24 hours and the inhibition was measured using a caliper, with extract samples carried out in triplicate. Based on the antibacterial effectiveness test of Tawandokulo Leaf Extract (Kleinhovia hospita Linn) against Streptcoccus mutans ATCC 25175 bacteria, the inhibition response results were obtained at concentrations of 20%, 40%, and 60%. The results obtained showed that the average diameter of the inhibition zone from the growth of Streptcoccus mutans ATCC 25175 bacteria obtained at 20% concentration had no inhibition zone, 40% concentration had no inhibition zone, 60% concentration had an average inhibition zone of 6,23 mm, positive control had an average inhibition zone of 19,13 mm, and negative control had no inhibition zone.